Searching for the Hidden God: the Intimacy of Sound and Listening among Krishna Devotees in Mayapur - Marje Ermel (Journal of Ethnology and Folkloristics)
This article looks at how the Krishna devotees in Mayapur, West Bengal, learn how to chant and listen to the sound of the holy name properly. They suggest that if one is ‘pure’ enough and knows how to listen one experiences the syneasthetic level of sound called pashyanti. At this level, one can reach beyond the duality of the ‘hidden and manifested’ worlds, the external and internal levels of sound; and one can ultimately see God face to face. This is also considered a level at which one can realise that the sound of God’s name and God himself are the same. I will focus on how the devotees learn to create this sense of intimacy with God through the sound of his holy name, and argue that listening is not merely a process connected to our auditory sense but rather a creative and engaging activity, a skill that one can develop.